Can you hear me now? Momentary increase in smartphone usage enhances neural processing of task-irrelevant sound tones - Mark van de Ruit; Arko Ghosh (Neuroimage: Reports, 2022)
According to popular belief when engaged on the smartphone surrounding information is ignored. However, emerging ideas based on laboratory-designed tasks suggest that the processing of task-irrelevant (distractor) information is enhanced when cognitive load is high as anticipated during intense periods of smartphone usage. Here we address the neural processing of task-irrelevant auditory tones while interacting with the smartphone touchscreen. We analyzed neural activity (EEG) while people (N = 24) were seated in public spaces and used their smartphones for ∼1.5 h. During this period, the number of touchscreen interactions spontaneously varied from one moment to another. The central and frontal theta-band (4–8 Hz) oscillations, an index of cognitive load, increased proportionally to the number of interactions. Moreover, an index of excitation:inhibition balance derived from the aperiodic signal components increased with the interactions. The auditory tones resulted in prominent evoked potentials with peaks at ∼50 ms, ∼100 ms, and ∼200 ms, reflecting the different cortical information processing stages. Of these, the ∼100 ms component was specifically related to the number of interactions such that the higher the number of interactions, the larger the neural signal amplitudes. Contrary to the popular notions but in keeping with emerging ideas on cognitive load, auditory information processing is enhanced with increased smartphone usage. In daily life, neural processing of the surroundings is partly shaped by the immediate cognitive demands imposed by the smartphone.